Testing the DRAMMA Model of Leisure and Subjective Wellbeing on College Students - Danny Twilley; Laura Morris; W. Hunter Holland (The Ohio State University Libraries, 2022)
Background: College students' declining mental health is a growing concern among institutions of higher education. Although many campuses have provided additional mental health counselors, identifying other mechanisms that facilitate and enhance mental health and wellbeing is also justified. Aim: Using the DRAMMA model as a theoretical framework, this research examined how leisure influences college students' subjective wellbeing. Methods: An online survey methodology was utilized to measure the psychological outcomes of leisure participation (DRAMMA), leisure satisfaction, and subjective wellbeing of 704 students attending a large 4-year Midwestern residential college. Results: This quantitative study found the five psychological mechanisms of the DRAMMA model (detachment-recovery, autonomy, mastery, meaning, and affiliation) influenced students' leisure satisfaction and subjective wellbeing. Conclusion: The findings support the need for higher education professionals to create leisure experiences that provide meaning and affiliation to promote subjective wellbeing and improve mental health.